On the possible role of stimulation duration for after-effects of transcranial alternating current stimulation - Strüber, Daniel; Rach, Stefan; Neuling, Toralf; Herrmann, Christoph S. (Frontiers in Cellular Neuroscience, 2015)
Transcranial alternating current stimulation is a novel method that allows application of sinusoidal currents to modulate brain oscillations and cognitive processes. Studies in humans have demonstrated tACS after-effects following stimulation durations in the range of minutes. However, such after-effects are absent in animal studies using much shorter stimulation protocols in the range of seconds. Thus, stimulation duration might be a critical parameter for after-effects to occur. To test this hypothesis, we repeated a recent human tACS experiment with a short duration. We applied alpha tACS intermittently for one second duration while keeping other parameters identical. The results demonstrate that this very short intermittent protocol did not produce after-effects on amplitude or phase of the electroencephalogram. Since synaptic plasticity has been suggested as a possible mechanism for after-effects, our results indicate that a stimulation duration of one second is too short to induce synaptic plasticity. Future studies in animals are required that use extended stimulation durations to reveal the neuronal underpinnings. A better understanding of the mechanisms of tACS after-effects is crucial for potential clinical applications.